IN SILICO STUDY OF ACRYLAMIDE TOXICITIES USING TOXTREE METHOD AND ITS ANALYSIS IN POTATO CHIPS USING HPLC METHOD - Sovia Aprina Basukia; Akhmad Aminur Rizqia; Engrid Juni Astuti; Rahmana Emran Kartasasmita; Riesta Prima Harinastitic; Juni Ekowati (UPT Penerbitan Universitas Jember)
Acrylamide is among the contaminants commonlypresent in the food due to processing. Acrylamide isclassified as a hazardous material which has potencyas human’s body carcinogenic for the case of cancerabout 2% per year in the world. Acrylamide wasfound in food processed by the high temperature(above 120ºC) in food with high carbohydratescontents, such as potato chips.Figure 1. The chemical structure of acylamideOBJECTIVESThe aim of this research was to obtain:- the toxicities of acrylamide and the functionalgroups or moieties responsible for thosetoxicities using Toxtree software.- analysis of acrylamide in potato chips using HPLC(High Performance Liquid Chromatography)method.